I married a witch - Smith, Thorne 1892-1934; Webb, Roy 1888-1982 (The Criterion collection, 2013)
Comedy about a witch who was burned at the stake 300 years ago. She plans to take revenge by marrying the descendent of her persecutors and ruining his political aspirations, but doesn't count on falling in love!